Familial Feeling Entangled Tonalities in Early Black Atlantic Writing and the Rise of the British Novel - Haschemi Yekani, Elahe (Springer Nature, 2021)
This open access book discusses British literature as part of a network of global entangled modernities and shared aesthetic concerns, departing from the retrospective model of a postcolonial "writing back" to the centre. Accordingly, the narrative strategies in the texts of early Black Atlantic authors, like Equiano, Sancho, Wedderburn, and Seacole, and British canonical novelists, such as Defoe, Sterne, Austen, and Dickens, are framed as entangled tonalities. Via their engagement with discourses on slavery, abolition, and imperialism, these texts shaped an understanding of national belonging as a form of familial feeling. This study thus complicates the "rise of the novel" framework and British middle-class identity formation from a transnational perspective combining approaches in narrative studies with postcolonial and queer theory.